Powściągliwość sędziowska w relacjach ze służbami specjalnymi : Konieczny czy obcy element demokracji? - Bernaczyk, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article poses the following research question: what forms and methods of exercising judicial power in relation to intelligence services serve as a litmus test for democratization or autocratization? A democratic system presupposes that the state’s activities are subject to judicial oversight. This stems from the concept of democracy as a regime governed by the rule of law, while arbitrariness characterizes the essence of authoritarianism. However, the oversight of intelligence services can be a deceptive indicator of the level of democracy, considering that the relationship between the controlling judiciary and intelligence services mirrors the recurring discourse on the role of the executive during a state of emergency. Threats to democracy in the 21st century are no longer limited to conventional armed conflicts or natural disasters governed by state of emergency procedures but increasingly resemble a perpetual confrontation between state structures and terrorism, hybrid conflicts, cyber conflicts, and proxy wars. Even with extreme forms of extrajudicial detention implemented during I & II World War, Western constitutionalism has not relinquished the rule of law, yet it has long tolerated solutions that leave the activities of intelligence services beyond effective control by other branches of power.
Keywords: służby specjalne; władza sądownicza; pozasądowe pozbawienie wolności; konstytucjonalizm; rządy prawa; informacje niejawne; aktywizm sędziowski; powściągliwość sędziowska